Generative AI as an Agent of Knowledge Socialization among Elementary School Students - Darman Manda; Dyan Paramitha Darmayanti; Iqbal Arifin; Ramdani Sidik (Celebes Journal of Elementary Education, 2026)
Generative artificial intelligence (Generative AI) such as ChatGPT, Gemini, and Meta AI is increasingly present in the lives of elementary school students, both through direct access and through various digital applications commonly used by families. Discussions of this phenomenon have so far been dominated by pedagogical and technological perspectives that view AI as a learning tool, while the social and cultural dimensions of children's interaction with AI have received relatively little attention. This study aims to examine the role of generative AI as an agent of knowledge socialization among elementary school students from a digital anthropology perspective. The method used is library research, with a narrative literature review of various sources published between 2020 and 2026, complemented by several foundational theoretical works as conceptual grounding. The findings show that generative AI cannot be understood merely as a technological tool. Its dialogic and personal mode of interaction leads children to perceive AI as a human-like figure and to position it as an authoritative source of knowledge. This condition enables AI to act as an agent of knowledge socialization, helping shape how children acquire, interpret, and internalize knowledge. The study also shows that the knowledge transmitted by AI is not neutral, as it is shaped by specific data, languages, and perspectives that do not always reflect the diversity of Indonesian culture. Based on these findings, the study proposes the concept of cultural-digital literacy as a framework to help children understand AI more critically, while preserving space for cultural diversity in the process of knowledge socialization in the digital era.